Design and characterization of 3D multilayer woven reinforcements shape memory polymer composites. (March 2021) - Goda, Ibrahim; Zubair, Zakariya; L'Hostis, Gildas; Drean, Jean-Yves
Shape memory polymer (SMP) composites are attractive and excellent smart materials due to their outstanding properties and rich functionality as they combine typical mechanical and functional properties of composites with shape memory properties. In particular, 3D reinforced preforms have tremendous potential for the development of functional composites by using the capabilities of 3D woven fabric preform design, and polymer shape memory behavior. Within that scope, this work aims to investigate the shape memory behavior and shape recovery properties of a specific type of 3D multilayer woven SMP composite in response to external stimuli. For this purpose, nine different multilayer stitched fabrics are produced with different weave structures, and different fabric thread densities using polyimide filaments. Then, a series of tests is carried out on these fabrics to evaluate their mechanical and physical properties. The layered fabric design that delivers high mechanical performance is next involved to manufacture the SMP composite samples, for which shape recovery capability is investigated. Fold-deploy and other shape memory cycle tests are performed to evaluate the shape memory characteristics. An optical 3D scanner based on fringe projection is further proposed to precisely acquire the geometry data and perform deformation analysis to quantitatively evaluate the shape fixity and shape recovery behaviors. The results from this study are very promising, demonstrating that these multilayer SMP structures can successfully be recovered following the desired design constraints without noticeable damage.